Oral Health Related Quality of Life among Completely Edentulous Patients using Geriatric Oral Health Assessment Index - Shrestha, Lajana; Dahal, Sirjana (Journal of Nepalese Society of Periodontology and Oral Implantology, 2019)
Introduction: Complete loss of teeth, though not life threatening, does have a significant impact on an individual, resulting in functional, psychological, and social limitations, affecting the quality of life and general health. Oral health related quality of life describes the outcomes of oral health conditions and therapy to those conditions. Objective: Geriatric Oral Health Assessment Index questionnaire (GOHAI) consists of 12 items that have an impact on quality of life of the older population, such as functional limitation, psycho-social limitation, and self-medication administered for dental pain. The study aimed to assess the effects of complete edentulousness before prosthodontic rehabilitation using GOHAI. Methods: Descriptive cross-sectional questionnaire study was done among 35 completely edentulous patients prior to prosthodontic rehabilitation using standardised GOHAI questionnaire consisting of 12 items and the twelfth item was eliminated due to its irrelevancy in the study group. Results: The mean age of the participants was 64.86±8.28 years with the mean duration of edentulousness of 4.02±5.4 years. The ability to swallow comfortably had highest mean GOHAI score (2.80±0.47) followed by use of medication to relieve pain and discomfort around the mouth. The least mean GOHAI score was found in trouble biting or chewing any kinds of food, such as firm meat or apples (1.26±0.56). However, the psychosocial impairment due to problems associated with complete edentulousness was less. Conclusion: Complete edentulousness was associated with impairment in physical functions like trouble in biting and chewing, with a need to limit the kinds and amount of food.